Taxonomy should be more photography based-eliminate need of physical specimen to study morphology - Chaladze, Giorgi (Zootaxa, 2017)
Recently, a new species of Diptera was described without preserving a type specimen (Evenhuis & Masrshall 2015). This publication caused controversy among taxonomists, of which many urged to restrict image-based descriptions to exceptional cases and insisted on the need to preserve specimens for future reproducibility of observations (Ceríaco et al. 2016; Krell 2016). I agree that type material is important in taxonomy for studying features that could not be captured on images. However, in the modern digital era, the need for actual specimen to study morphology can be circumvented.